Behavior of large shaft sinking headframe subjected to uneven foundation settlement - Wang, Bo; Liu, Zhiqiang; Yuan, Shuai (Frontiers in Earth Science, 2022)
Shaft sinking headframe plays a key role in shaft construction as the support structure for hoisting and suspending equipment. Recently, effect of uneven foundation settlement on shaft sinking headframe has been much concern when sinking shafts by freezing sinking method or in permafrost soil areas. In this paper, FE calculation was performed to investigate the mechanical behaviour of the SA-3 shaft sinking headframe under uneven foundation settlement (0.001L-0.006L) and normal working-load condition. The results indicate that the most unfavorable condition for stress of members is the diagonal double foundation settlement and in the view of geometric offset, the most unfavorable condition is the same-side double foundation settlement. The corner members near the settled foundation were changed from compression state to tension state. Uneven foundation settlement less than 0.001L is acceptable for the safety and good service performance of the shaft sinking headframe. This criterion is consistent with the limitation in standard for design of the mine headframes and can be used for reference in engineering practice.